(untitled) (Global Journal of Management and Business Research, 2023)
Mobile Economy Maximation Bundles are theoretical all-inclusive bundling packages, curated to out-of-town travelers coming into a specific municipal city for a live music event. The packages include hotel stays, base and premium food options and tickets to the event itself, dynamically priced based on forecasted demand by a demand rate . Bundles would open to public sale at a pre-destined time, but because hotels will be able to buy a select number of tickets ahead of time, they do not need to contend with the general sale, giving them a fixed number of tickets at MSRP prices which can be passed to the customer, and customers would gravitate to hotel providers offering this system over competitors who do not. The structuring of these entertainment bundles is an effort to improve the experience for traveling consumers but also a response to rising scalper prices of concert tickets where, in 2023, in-demand concerts such as the Taylor Swift Era’s Tour, scalper tickets were priced anywhere from 614.29% to 2665.1% higher than their original MSRP price, prompting a critical need to address the rising costs to consumers.